Backstage Pizza [window sign] (1995)
View of illuminated neon sign at window of Backstage Pizza campus dining facility across from the campus bookstore in the University Union. Other items in the window include announcements on quarter break hours for the 1994-1995 school year and a notice that the facility is closed during the summer season.